Stress Physiology of Tea in the Face of Climate Change (Springer Singapore, 2018)
This book focuses on the existing knowledge regarding the effect of global climate change on tea plant physiology, biochemistry, and metabolism as well as economic and societal aspects of the tea industry. Specifically, this book synthesizes recent advances in the physiological and molecular mechanisms of the responses of tea plants to various abiotic and biotic stressors including high temperature, low temperature or freezing, drought, low light, UV radiation, elevated CO2, ozone, nutrient deficiency, insect herbivory, and pathogenic agents. This book also discusses challenges and potential management strategies for sustaining tea yield and quality in the face of climate change. Dr. Wen-Yan Han is a Professor and Dr. Xin Li is an Associate Professor at the Tea Research Institute of the Chinese Academy of Agricultural Sciences (TRI, CAAS), Hangzhou, PR China. Dr. Golam Jalal Ahammed is an Associate Professor at the Department of Horticulture, College of Forestry, Henan University of Science and Technology, Luoyang, PR China.